2000
DOI: 10.3390/50300512
|View full text |Cite
|
Sign up to set email alerts
|

Binding Constant of Amines to Water/AOT/n-Hexene Reverse Micelles. Influence of the Chemical Structure

Abstract: Abstract:The distribution of different amines between n-hexane bulk and the micellar pseudophase of AOT reverse micelles were measured by a fluorometric method. An independent method was used to corroborate the incorporation of the amines to the interface. The effect of the amine structure on the binding constant was analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…On the other hand, the reported data are relevant for the quantitative description of processes involving amines as reactants and taking place in reverse micelles, such as the S N Ar [18][19][20][21] or aminolysistype reactions that have biological relevance [28,29]. Moreover, it is also showed that the studied amines are not protonated inside the (AOT)/n-hexane reverse micelles, which is a very interesting result dealing in reactivity of these substrates as nucleophiles [18][19][20][21]28,29].…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…On the other hand, the reported data are relevant for the quantitative description of processes involving amines as reactants and taking place in reverse micelles, such as the S N Ar [18][19][20][21] or aminolysistype reactions that have biological relevance [28,29]. Moreover, it is also showed that the studied amines are not protonated inside the (AOT)/n-hexane reverse micelles, which is a very interesting result dealing in reactivity of these substrates as nucleophiles [18][19][20][21]28,29].…”
Section: Introductionmentioning
confidence: 72%
“…However, no hydrolysis had been detected for previously studied S N Ar reactions of aliphatic amines with halo-nitrobenzene compounds in water/AOT/ n-hexane [18][19][20] or in reaction of nitrosation of amines in water/AOT/isooctane [28,34]. Moreover, the partition constants obtained in this work for n-BA and PIP are coherent with the values previously calculated from kinetic data for the S N Ar reaction with 1-chloro-2,4-dinitrobenzene [19] and 1-fluoro-2,4-dinitrobenzene [18,20] in the same reverse micellar system. To further check the possible influence of amine hydrolysis, K was measured for i-BA with the Ru(bpy) 2+ 3 -Fe(CN) 3− 6 at pH 12.…”
Section: Determination Of the Partition Constantsmentioning
confidence: 79%
See 3 more Smart Citations